Impacts of the representation of riverine freshwater input in the community earth system model. (September 2016) - Tseng, Yu-heng; Bryan, Frank O.; Whitney, Michael M.
Highlights: Horizontal and vertical spreading of riverine freshwater strongly impacts SSS. Vertical spreading has largest impact when penetration depth is comparable to MLD. A globally conservative virtual salt flux with local reference SSS is presented. Abstract: The impacts of the representation of riverine freshwater input on the simulated ocean state are investigated through comparison of a suite of experiments with the Community Earth System Model (CESM). The aspects of river and estuary processes investigated include lateral spreading of runoff, runoff contribution to the surface buoyancy flux within the K-Profile Parameterization (KPP), the use of a local salinity in the virtual salt flux (VSF) formulation, and the vertical redistribution of runoff. The horizontal runoff spreading distribution plays an important role in the regional salinity distribution and significantly changes the vertical stratification and mixing. When runoff is considered to be a contribution to the surface buoyancy flux, the calculation of turbulent length and velocity scales in the KPP can be significantly impacted near larger discharge rivers, resulting in local surface salinity changes of up to 12 ppt. Using the local surface salinity instead of a globally constant reference salinity in the conversion of riverine freshwater flux to VSF can reduce biases in the simulated salinity near river mouths but leads to drift in global mean salinity. This is remedied through a global correction approach. We also explore the sensitivity to the vertical redistribution of runoff, which partially mimics the impacts of vertical mixing process within estuaries and coastal river plumes. The impacts of the vertical redistribution of runoff are largest when the runoff effective mixing depth is comparable with the mixed layer depth, resulting from the enhanced vertical mixing and the increase of the available potential energy. The impacts in all sensitivity experiments are predominantly local, but the regional circulation can advect the influences downstream.